Perception of students of medicine of a public university on the elderly professor and the elderly citizen - Martina, Martha (2014)
Introduction: Most available studies show that youngsters’ perception on old age is usually negative. Aim: To analyze the perception of Universidad Nacional Mayor de San Marcos’ medical students on old age, and to analyze the presence of negative stereotypes towards old age and elder teachers’ faculties. Design: Cross-sectional study. Location: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: First, third and fifth year medical students. Interventions: A self-administered questionnaire using a semantic differential scale to determine student’s perception of the elderly was applied. Main outcome measures: Perception of the elder teachers’ faculties and the elderly. Results: From the 319 students sampled 54.2% were male and mean age was 21.7± 2.6 years old; 90.3% had proximity to teachers older than 70. Fifth year students gave lower scores for both elder teachers (p=0.003) and older adults (p=0.045). Students living with persons older than 70 in their families had a more positive perception on older adults (p=0.037). In regards to older teachers, five characteristics obtained a perception score over 70%: self security (78%), organized (73.9%), interest in students’ learning (72.8%), planning (72.6%), and emotional stability (71.8%). Regarding the elder in general, scores did not reach 70%, and they were characterized as tractable, sociable and skillful. Conclusions: Medical students showed a positive perception of elder teachers and elderly in general. There were statistically significant differences by year of studies. Students that lived with elder people had a more favorable perception on both old age and elder teachers, as compared with those who did not have such experience.